Biophysical characterization of cofilin-induced extension–torsion coupling in actin filaments. Issue 9 (14th June 2016) - Kim, Jae In; Kwon, Junpyo; Baek, Inchul; Na, Sungsoo
Abstract: Cofilin makes the actin filament flexible and thermally unstable by disassembling the filament and inducing bending and torsional compliance. Actin monomers bound to cofilin are able to chemically and mechanically interact in response to external forces. In this study, we performed two molecular dynamics tensile tests for actin and cofilactin filaments under identical conditions. Surprisingly, cofilactin filaments were found to be twisted, generating shear stress caused by torsion. Additionally, analysis by plane stress assumption indicated that the extension–torsion coupling effect increases the amount of principal stress by 10%. Using elasticity and solid mechanics theories, our study elucidates the role of cofilin in the disassembly of actin filaments under tensile forces.